Control of allergic rhinitis in four latin american countries: Rinola study - Silva, Diana L; de Barayazarra, Susana; Valero, Antonio; Garcia, Elizabeth; Uriarte, Silvia; Peñaranda, Augusto; Chapman, Edgardo; Garcia, Maria B; Ocampo, Jaime; Valencia, Viviana; Moreno, Sergio; Corelli, Silvana; et al. (Frontiers in Allergy, 2022)
Background: Allergic rhinitis (AR) affects up to 40% of general population, there are large-scale multicenter studies that described its characteristics, few studies focused on studying patients with AR in Latin America (LA). Methodology: A cross-sectional, descriptive, multicenter study was carried out in four LA countries (Colombia, Argentina, Cuba and Peru). Patients diagnosed with AR between November 2017-June 2020 were included. Sociodemographic and clinical data, sensitization profile and current treatment were collected in the Electronic Data Collection (BDClinic). Patients filled this questionnaires: Rhinitis Control Assessment Test (RCAT), Reflexive Total Nasal Symptom Score (rTNSS), Modified ARIA Criteria for AR Severity (mARIA) and ESPRINT-15. Results: Study included 412 patients. Median age was 25 years (15-39). Nasal obstruction was present in 303 patients (73.5%). 334 patients (81%) had a persistent AR. 121 patients (31.3%) had asthma. Most frequently positive skin tests were: Dermatophagoides pteronyssinus in 365 (88.6%) and Dermatophagoides farinae in 331 patients (81.3%). 411 patients (99%) reported that AR affected their quality of life. Median score of ESPRINT-15 was 1.87 (0.93-2.93), Mean values of RCAT and rTNSS were 19.01 (± 4.59) and 5.4 (± 2.97). 215 patients (60%) were receiving oral antihistamines. Physicians decided start nasal corticosteroids in 296 (71.8%). 70 patients (16.9%) were receiving immunotherapy. Conclusion: These findings confirm that most of patients with AR in LA have a persistent disease with negative impact on quality of life. Dust mites are the main sensitizers. These findings will allow know the true impact of AR and can lead to a better disease management.